Категорія повторюваності: мовний та мовленнєвий виміри - Пахолок, Зінаїда Олександрівна; Pakholok, Z. O. (Київський національний університет імені Тараса Шевченка, 2015)
Дисертаційна робота є першим системним аналізом структурних типів і функціональних реалізацій категорії повторюваності у мові та мовленні. Досліджується об’єктивна закономірність, притаманна всім об’єктам і явищам матеріального світу, яка полягає у відтворенні об’єкта чи явища частково або повністю. Повторюваність виступає як об’єктивна реальність, яку людина несвідомо засвоює в міру набуття досвіду. Здатність до повторення можна інтерпретувати в термінах архетипів людської свідомості. На основі об’єднання різних видів мовних і мовленнєвих повторів у загальну систему повторів розкривається їх позамовна сутність і першооснова: коливання, вібрація, ритм, чергування. Категорія повторюваності пронизує не тільки всі рівні мовної системи, але й всі грані людського буття: фізичного, фізіологічного, психічного, біологічного, соціального та культурного. Нова концептуальна схема розв’язання проблеми категорії повторюваності базується на визнанні ізоморфізму онтологічної природи фізичного, психологічного та мовного простору як реалізації цієї категорії у Всесвіті.

The thesis is devoted to investigation of the category of repetition (CR) in the broad scientific context on the crossways of different scientific approaches and understandings. Above this, it appears to be the first systematic analysis of structural types and functional implementations of the CR in language and speech done on the material of more than 50 languages. The new conceptual solution pattern of the category of repetition investigation is based on the recognition of the ontological isomorphism of physical, psychological and linguistic spaces within which the CR is realized as the universal one. The objective law of repetition inherent for all objects and phenomena of the material world is being studied. Repetition appears to be a kind of objective reality which person unconsciously aquires in the processes of gaining experience. Repetition therefore has as its ground what we call archetypes of human consciousness. Integrative methodics of language and speech repeats’ description gives an opportunity to reveal their extra-linguistic nature and original base: fluctuations, vibration, rhythm, alternating. Category of repetition not only transfuses all levels of the language system, but also all possible facets of human existence: physical, physiological, mental, biological, social and cultural. CR is implemented with the help of a wide repertoire of language and speech means of expression. Such basic language system units as phoneme, syllable, morpheme, word, phrase and sentence appear to be these means of CR manifestation. On the level of speech CR is implemented by figures of word and thought, which might take both positive and negative stylistic functions. The systemic nature of poetic repetition has been demonstrated that created grounds and prospectives for generating the wholistic theory of repetition in future. In the frames of literary works of art CR works as marker of recurrent representation of semantic components belonging to the deep structure of the text, which is realized by units of different language levels and both appears to be a mean for conveyance of emotionally expressive information to the reader. The high degree of saturation of different speech genres with CR units might be explained by universal character of this category. The reason for its spreadness hides in onthologically formed ways of reality reflection: behavioral imitation (imprinting) and learning based on repetition. In the adult age, such kind of reflection leads to the development of stereotypes. Integral description of the immanent semantic content of CR, attempts made for differentiation of these values and lexical tools used for manifestation of different types of repetition semantics, give all reasons to qualify CR as unique language and speech phenomenon, which needs futher systematic and conceptual study.
Repeatability category: language and speech measurements
Keywords: категорія повторюваності; періодичність; циклічність; наслідування; ритм; види повторів; мовна універсалія; category of repetition; periodicity; cycling; imitation; rhythm; linguistic universal; types of repetition